2012
DOI: 10.1042/bj20112000
|View full text |Cite
|
Sign up to set email alerts
|

A novel non-canonical mechanism of regulation of MST3 (mammalian Sterile20-related kinase 3)

Abstract: The canonical pathway of regulation of the GCK (germinal centre kinase) III subgroup member, MST3 (mammalian Sterile20-related kinase 3), involves a caspase-mediated cleavage between N-terminal catalytic and C-terminal regulatory domains with possible concurrent autophosphorylation of the activation loop MST3(Thr178), induction of serine/threonine protein kinase activity and nuclear localization. We identified an alternative ‘non-canonical’ pathway of MST3 activation (regulated primarily through dephosphorylat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
54
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(55 citation statements)
references
References 75 publications
1
54
0
Order By: Relevance
“…95 GCK-III kinases may target the Golgi apparatus through binding with GM130 ( Figure 3). 53,96 Despite forming a stable complex, PDCD10 and Striatin may differentially regulate GCK-III. For example, PDCD10 knockdown promotes Golgi localization of MST4 in HeLa cells.…”
Section: Gcks In Immune Regulationmentioning
confidence: 99%
“…95 GCK-III kinases may target the Golgi apparatus through binding with GM130 ( Figure 3). 53,96 Despite forming a stable complex, PDCD10 and Striatin may differentially regulate GCK-III. For example, PDCD10 knockdown promotes Golgi localization of MST4 in HeLa cells.…”
Section: Gcks In Immune Regulationmentioning
confidence: 99%
“…Recently it has been reported that in addition to autophosphorylating on Thr178 of its activation loop, MST3 also autophosphorylates on Thr328 which is located just after the WIF motif (sequence WIF T I) [24]. Clearly these sequence motifs have a strong resemblance to each other, being of the form Φx (1−2) Φ T Φ where Φ is a hydrophobic residue.…”
Section: Resultsmentioning
confidence: 99%
“…It might also be involved in stabilizing the protein. Another Ste20 kinase was recently shown to autophosphorylate on a comparable C-terminal site (45). The phosphorylation itself was not thought to directly change activity, but was proposed to be involved in docking CAB39 (44).…”
Section: Discussionmentioning
confidence: 99%